Acoustic complexity indices reveal the acoustic communities of the old-growth Mediterranean forest of Sasso Fratino Integral Natural Reserve (Central Italy). (January 2021) - Farina, A.; Righini, R.; Fuller, S.; Li, P.; Pavan, G.
Highlights: The Sasso Fratino Natural Reserve (Central Italy) is a rare example of climax Mediterranean forest. Acoustic Complexity Indices (AS, EE, ASD, fractal dimension of EE, ASD) are used. EE and ASD added further details on the daily evolution of the overall soundscape. Fractal dimension of EE, ASD provided further information that enriched the representation of AS. Abstract: The Sasso Fratino Integral Natural Reserve (Central Italy), a rare example of climax Mediterranean forest, provides an extraordinary opportunity to create an important soundscape reference of old-growth forest. In this study, we describe the soundscape of three localities (Lama, Sasso 950, Sasso 1400) representative of a gradient of variety and complexity of habitats, recorded during the period 10 May to 9 June 2017. Our results reveal temporal partitioning into acoustically homogeneous periods across 24 h suggesting that soniferous species (mainly birds) adopt ecological routines in which their acoustic activity is organized according to specific transient physiological needs. We processed multi-temporal aggregates of 1, 5, 10, and 15 s recordings and calculated the Acoustic Signature ( AS ) with four new indices: Ecoacoustic Events ( EE ), Acoustic Signature Dissimilarity ( ASD ), and their fractal dimensions ( DEE and DASD ), derived from the Acoustic Complexity Index ( ACI ). The use of the EE and ASD greatly improved the AS interpretation, adding further details such as the emergence of a clear sequence of patterns consistent with the daily evolution of the overall soundscape. DEE and DASD confirm the patterns observed using the AS, but provide more clarity and detail about the great acoustic complexity that exists across temporal scales in this old-growth forest. The temporal turnover of different acoustic communities occurs as a result of a gradual shift of different homogenous acoustic properties. We conclude that soniferous species use distinct, species-specific temporal resolutions according to their physiological and ecological needs and that the fractal approach used here provides a novel tool to overcome the difficulties associated with describing multi-temporal acoustic patterns.